2006
DOI: 10.4049/jimmunol.176.5.2799
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Induced Transplantation Tolerance That Is Dependent on Thymus-Derived Regulatory T Cells

Abstract: Targeting of the CD45RB isoform by mAb (anti-CD45RB) effectively induces donor-specific tolerance to allografts. The immunological mechanisms underlying the tolerant state remain unclear although some studies have suggested the involvement of regulatory T cells (T-regs). Although their generative pathway remains undefined, tolerance promoting T-regs induced by systemic anti-CD45RB treatment have been assumed to originate in the peripheral immune system. We demonstrate herein that separable effects on the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
(34 reference statements)
0
29
0
Order By: Relevance
“…Because CTLA-4 can deliver negative signals in T cell activation and may be expressed by regulatory T cells (Tregs), 6 anti-CD45RB-induced up-regulation of CTLA-4 may play an important role in deactivation of graft-reactive lymphocytes (8,9). In addition, induction of T cell anergy and formation of Th2 or Treg cells have been suggested in previous studies (4,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because CTLA-4 can deliver negative signals in T cell activation and may be expressed by regulatory T cells (Tregs), 6 anti-CD45RB-induced up-regulation of CTLA-4 may play an important role in deactivation of graft-reactive lymphocytes (8,9). In addition, induction of T cell anergy and formation of Th2 or Treg cells have been suggested in previous studies (4,10).…”
mentioning
confidence: 99%
“…Thus, CD45 serves as a rheostat that determines the overall sensitivity of the adaptive immune system to antigenic stimulation. Given its crucial role in lymphocyte activation, CD45 has been targeted with therapies that have emerged as potent immunosuppressive agents in both autoimmune and transplant models (4,5).…”
mentioning
confidence: 99%
“…42,43 Anti-RB treatment is useful as an immunotherapeutic agent and induces transplant tolerance. 39,[44][45][46][47] It must be stressed that B cells play a critical role in these processes. 48 Therefore additional studies into the impact of CD45RB ligation on the surface of B cells are needed.…”
mentioning
confidence: 99%
“…A previous study utilizing CD45RB mAbs showed that tolerance could not be achieved in aged mice due to thymic atrophy (24), because this mode of tolerance induction requires an active thymus to produce new Tregs (38). In the present study, 100% of aged mice became tolerant to allogeneic skin grafts, suggesting that tolerance induction in our model is not hindered by thymic atrophy and/or compensated by peripheral mechanisms.…”
Section: Discussionmentioning
confidence: 47%
“…Models of transplantation tolerance that do not depend on BMT-induced mixed chimerism have also demonstrated a requirement for an active thymus (24,38,39). To determine the role of intrathymic deletion in this model, 2-month-old mice were Tx prior to BMT (as aged mice did not recover from thymectomy under general anesthesia in our experience).…”
Section: Discussionmentioning
confidence: 99%